Protocol for the development of a core outcome set for the optimisation of treatment and follow-up of patients with an anorectal malformation (ARM): The ARM and OUtcome Review (ARMOUR)-project - Layla Hassan; Shauna A M Cortenraad; Charlotte B M Rosenberg; Merel L Kimman; Michel Haanen; Wim G van Gemert; Ruben Gerardus Johannes Visschers (BMJ Publishing Group, 2023)
Background Primary treatment of an anorectal malformation (ARM) is surgical restoration of the anatomy. These children can experience many problems later in life; therefore, a long-term follow-up by an experienced team is needed. The aim of the ARM and OUtcome Review (ARMOUR-study) is to identify the lifetime outcomes that are important from a medical and patients' perspective and develop a core outcome set (COS) that can be implemented in a care pathway to support individual ARM management decisions.Methods First, a systematic review will identify clinical and patient-reported outcomes described in studies conducted in patients with an ARM. Second, qualitative interviews with patients of different age categories and their caregivers will be held to ensure that the COS will include outcomes that are relevant from the patient's perspective. Finally, the outcomes will be taken forward to a Delphi consensus exercise. Using multiple web-based Delphi rounds, key stakeholders (medical experts, clinical researchers and patients) will prioritise outcomes. During a face-to-face consensus meeting, the final COS will be determined. These outcomes can be evaluated in a life-long care pathway for patients with ARM.Discussion The development of a COS for ARMs aims to reduce heterogeneity in outcome reporting between (clinical) studies, enhancing the availability of comparable data, which will facilitate evidence-based patient care. Assessment of the outcomes in the COS during individual care pathways for ARM can support shared decisions regarding management. The ARMOUR-project has ethical approval and is registered with the Core Outcome Measures in Effectiveness Trials (COMET) initiative.Level of evidence Treatment study level II.